Ochyronemus, a New Genus of the Tarsonemid Tribe Pseudotarsonemoidini (Acari: Heterostigmatina) from Mexico - Magowski, Wojciech Ł.; Rezende, Jose M. [UNESP]; Ochoa, Ronald (MDPI, 2025)
A new genus for the tribe Pseudotarsonemoidini of the family Tarsonemidae is established in order to accommodate undescribed mites associated with bark beetles in Mexico. The new, monotypic genus Ochyronemus, with the type species O. jaliscoe being diagnostically and phylogenetically closest to the derived Pseudotarsonemoides-Tarsobisulcus cluster of the Pseudotarsonemoidini, possesses an intermediate position between these two genera. Details of the morphology related to its genus-level affiliation, primarily tibiotarsal I claw and leg setation, are compared in the context of the other genera of the tribe.
Keywords: bark beetles; galleries; tarsonemid mites; wood boring insects